ANALYSIS OF RECOVERY MOTIVATION IN DRUG ABUSE CASES INJURED REHABILITATION IN PRISON - Aeni, Nurul (Rifapublisher.id, 2025)
Background: Motivation to recover for drug abusers in prison have psychological and social challenges in their recovery process. motivation to recover from drug addiction is the key to designing an effective and comprehensive rehabilitation program. Objective: This study aims to analyze the motivation to recover in prisoners involved in drug abuse cases at Class II B Polewali Penitentiary. Motivation to recover is a crucial aspect in the rehabilitation process for individuals facing drug addiction, especially in a prison environment that is often full of psychological and social challenges. Method: This study uses a descriptive analytical approach with an observational study design, involving 40 prisoners as samples. The sampling method was carried out using total sampling, which includes the entire population of drug abuse prisoners in the prison. The results of the analysis show that the majority of respondents are between 20 and 44 years old, with most having a prison term of 1-5 years. Result: In terms of motivation to recover, it was found that 57.5% of respondents were at the precontemplation stage, indicating that they had not fully realized or considered the need for positive behavioral changes. Meanwhile, 42.5% of respondents were at the contemplation stage, where they began to realize the problem and consider changes. Conclusions: This study identified that motivation to recover is greatly influenced by several factors, including the length of detention, psychological conditions, and the prison environment. Prisoners with longer prison terms tend to experience a decrease in the frequency of drug use, but many still have not reached the preparation or action stage in the process of changing behavior. In addition, psychological conditions such as anxiety and depression, as well as the prison environment that may exacerbate stress, also contribute to low motivation to recover. These findings emphasize the importance of a more comprehensive approach to supporting the rehabilitation process of drug abuse prisoners. More effective interventions are needed to increase prisoners' awareness and readiness for recovery.